PENGARUH KEPEMILIKAN PERUSAHAAN DAN MANAJEMEN LABA TERHADAP TIPE AUDITOR DAN AUDIT FEES PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Tirta Luhur Pambudi; Imam Ghozali (Diponegoro Journal of Accounting, 2013)
This study aims to examine the impact of firm ownership type and earning management to the auditor relationship in manufacturing companies. Firm ownership type in this paper was divided into two; stated-owned and private-owned; earnings management was measured by discretionary accruals using the Modified Jones Model. Auditor relationships referred to in this paper is the type of auditor and audit fees. Auditor is classified into two types, domestic auditor and foreign auditor. An audit fee was measured by natural logarithm professional fees contained in the financial statements. Using professional fees as proxy for audit fees because in Indonesia still few company disclose their audit feeson their financial statements. Population of this paper is a manufacturing company listed on the Indonesia Stock Exchange (IDX) period of 2011. Total sample is 85 firms. The hypotheses in this study were tested by logistic regression analysis and multiple regressions.The results of this study indicate that the firm ownership type by the state or private ownership does not affect the probability and magnitude of auditor election audit fees. Research also shows that a higher of earnings management does not affect the probability of selection auditor. While the level of earnings management affects the amount of audit fees paid.